JS07.5.A 18F-fluciclovine PET and multi-parametric MRI to distinguish pseudoprogression from tumor progression in post-treatment glioblastoma. (5th September 2022) - Nabavizadeh, A; Bagley, S; Doot, R; Ware, J; Young, A; Ghodasara, S; Zhao, C; Anderson, H; Schubert, E; Henderson Jr, F; Pantel, A; Chen, H; et al.
Abstract: Background: Differentiation of tumor progression (TP) from pseudoprogression (PsP) is a major unmet need in glioblastoma (GBM). 18 F-Fluciclovine is a synthetic amino acid PET radiotracer with higher uptake in tumor tissue vs. areas of treatment-related change. We aimed to assess the combined value of 18 F-Fluciclovine PET and multi-parametric MRI for differentiating PsP from TP. Material and Methods: We enrolled 30 patients with GBM with a new or enlarging contrast-enhancing lesion on MRI after chemoradiotherapy who were planned for surgical resection of the lesion. Patients underwent pre-operative 18F-Fluciclovine PET and multi-parametric MRI. Following surgery, the relative percentages of viable tumor and therapy-related changes observed on histopathology were quantified. Patients were categorized as TP if viable tumor represented ≥ 50% of the specimen, mixed TP if < 50% and > 10%, and PsP if ≤ 10%. SUVmax, SUVpeak, and 50% threshold SUVmean were calculated and normalized to contralateral brain, pituitary gland, and superior sagittal sinus (SSS). The least absolute shrinkage and selection operator (LASSO) was used to determine the variables most predictive of tumor percentage. The strength of association between the primary outcome and selected variables was assessed by Pearson's or Point-biserial correlation. Results: 18 patients with TP, 4 with mixed TP-PsP, and 8 with PsP were included. There was a positive correlation between 50% threshold SUV mean measured from PET images acquired 50-60 minutes post-injection and rCBVmax by MRI and tumor percentage by histology (r= 0.56; p= 0.004 and r=0.50; p=0.012 respectively). 40-50 minutes SUVmax (OR=1.78 rpb =0.51) and rCBVmax (OR=1.64, rpb =0.48) were positively correlated with tumor TP/mixed TP group. Patients who demonstrated TP/mixed TP-PsP had significantly higher 40-50 minutes SUVmax compared to patients with histological PsP (6.71±2.03 vs 3.93±1.63; p=0.012). 40-50 minutes SUVmax cut-off of 4.46 provided 90% sensitivity and 80% specificity for differentiation of TP/mixed TP-PsP from PsP (AUC=0.88). Combining a 40-50 minutes SUVmax cut-off of 4.46 and an rCBVmax cut-off of 3.67 provided 100% sensitivity and 100% specificity for differentiating TP/mixed TP-PsP from PsP (AUC=1). Patients who demonstrated TP had a significantly higher 40-50 minutes SUVmax compared to patients with histological PsP (6.99±2.06 vs 3.93±1.63; p=0.008). A 40-50 minutes SUVmax cut-off of 4.66 provided 94% sensitivity and 80% specificity for differentiation of TP from PsP (AUC=0.89). Conclusion: 18F-Fluciclovine PET uptake is positively correlated with viable tumor quantification on histology and can accurately differentiate PsP from TP in patients with GBM. Further independent studies are required to cross-validate these promising early results.